Dual Drug Loaded, pH-Sensitive Metal-Organic Particles for Synergistic Cancer Therapy - Wu, Shichao; Hu, Shuo; Yang, Xiangrui (Frontiers in Bioengineering and Biotechnology, 2022)
The strategy for dual drug loaded nanomedicine with targeting property was always complex. Here, a novel strategy for the preparation of metal organic particles (MOPs) based nanomedicine was developed, with which combretastatin A4 (CA4) and mitoxantrone (MIT) loaded MOPs (CMMOPs) were obtained. In this system, using merely Cu(II) as a bridge to connect and coordinate with the dual drugs, the CMMOPs possessed a fairly high drug loading of almost 90%. What’s more, the coordination between Cu(II) and the drugs was stable at physiological pH but easily cleavable at the tumor acidic microenvironment, which would provide a good targeting property for the CMMOPs. And the in vivo experiments indicated that the CMMOPs possessed a significantly enhanced antitumor efficiency with negligible side effects. The results suggest that the CMMOPs could be a potential anticancer formulation for tumor-targeted drug delivery.